2013
DOI: 10.1371/journal.pone.0075364
|View full text |Cite
|
Sign up to set email alerts
|

Both Enhanced Biocompatibility and Antibacterial Activity in Ag-Decorated TiO2 Nanotubes

Abstract: In this study, Ag is electron-beam evaporated to modify the topography of anodic TiO2 nanotubes of different diameters to obtain an implant with enhanced antibacterial activity and biocompatibility. We found that highly hydrophilic as-grown TiO2 nanotubes became poorly hydrophilic with Ag incorporation; however they could effectively recover their wettability to some extent under ultraviolet light irradiation. The results obtained from antibacterial tests suggested that the Ag-decorated TiO2 nanotubes could gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 43 publications
5
50
0
Order By: Relevance
“…This can be done by tailoring topography on the nanoscale [12,35,36], by incorporating varied amounts of Ag in similar structures [13,16,37,38], or by pursuing alternative strategies for antibacterial surfaces, thoroughly surveyed in recent reviews [10,[14][15][16]22]. Although history has proven that with persistence and some chance, great discoveries can be made, the possibility of this occurring will undoubtedly be greater if more parameters can be screened in a faster and cheaper way [17,18,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by tailoring topography on the nanoscale [12,35,36], by incorporating varied amounts of Ag in similar structures [13,16,37,38], or by pursuing alternative strategies for antibacterial surfaces, thoroughly surveyed in recent reviews [10,[14][15][16]22]. Although history has proven that with persistence and some chance, great discoveries can be made, the possibility of this occurring will undoubtedly be greater if more parameters can be screened in a faster and cheaper way [17,18,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…As well, comparing Ag + release data and corresponding in vitro or in vivo response in the literature should be done cautiously, as quantification methods tend to vary among studies. The cytotoxicity and tissue cell response of novel Ag-TiO 2 nanotube coatings have been evaluated in recent studies, and demonstrated that a controlled release of Ag + can have sufficient antibacterial effect while maintaining, or in some instances even improving the biocompatibility [36,38,56]. The biological evaluation of the gradient coating presented in this work was limited to the effect against S. aureus bacteria, precluding the authors from drawing any conclusions regarding the mammalian cell response to the amount of Ag + released.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, to avoid their susceptibility to abrasion 5 and poor resistance to crack propagation, due to a highly cross-linked structure, 6 the basic idea is to enhance the mechanical properties and to promote the surface compatibility of the coating by incorporating different nanofillers. [7][8][9][10][11][12][13][14][15][16] It is mainly the favourable effects of the particle size, the volume fraction and the size distribution on the mechanical properties of composite coatings that have been studied. [17][18][19][20][21][22] Z.…”
Section: Introductionmentioning
confidence: 99%
“…1 The interaction of nanoscale surface topographies with cells was proven to play a crucial role in the biocompatibility of implants. 2 Various nanoscale surface modifications have been proposed in order to enhance the biocompatibility and antibacterial activity of medical implants. 3 Epoxy resins are widely used as long-term protective coatings for stainless steels in various applications.…”
Section: Introductionmentioning
confidence: 99%